PENERAPAN MODEL PEMBELAJARAN BAMBOO DANCING UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS DI SMA - Marselina Yeni; Warneri Warneri; Rum Rosyid (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractPurpose of this research is to know the increasing of students’ critical thinking ability in using Bamboo Dancing in grade IX IPS D SMAN 1 Sengah Temila in economic lesson and the acrivity is using learning model of Bamboo Dancing.Kind of this research is Clasroom Action Research design by Kemmis and Mc Tanggartwhich is including four steps,they are planning, Implementation, observation, and reflection. Subject of this research is 35 students of grade XI IPS D.Techniques of taking the data are observation, documentation, and test. Technique of quantitative data analysis is descriptive statistic analysis.The result of research is implementation of Bamboo Dancing increase ability of students' critical thinking, complete category in pre-cicleIs 54,28%, uncompleted category is 45,71%, implementation of cycle I is 60% complete category, 40% uncompleted category, implementation of cycle II is 88,57 complete category, 14,29 uncompletef category.Implementation of learning used Bamboo Dancing model in economy lesson into students' of SMAN 1 Sengah Temila Is well done. In cycle I, result of implementation is 73,3% In good category. In cycle II, the implementaion is increse, 91,6% in very good category. Keywords: Bamboo Dancing, Cooperative Learning, Critical Thinking .